2013
DOI: 10.2340/00015555-1501
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histological Prognostic Factors for Local Recurrence and Metastasis of Cutaneous Squamous Cell Carcinoma: Analysis of a Defined Population

Abstract: Cutaneous squamous cell carcinomas (cSCC) can recur locally and can metastasize. The objective of this study was to identify clinical and histopathological prognostic factors for local recurrence and metastasis in cSCCs at any body site. Clinical and histopathological data were collected from 224 patients with cSCC. During the median follow-up period of 43 months (range 0-73 months) the cumulative probabilities of recurrence-free survival at 1, 2 and 4 years post-treatment were 98.0%, 96.9% and 94.7%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 26 publications
3
39
0
2
Order By: Relevance
“…For the purpose of the present study, PNI was analyzed as a binary variable, including 6 articles, and was associated with an RR of local recurrence (RR [95% CI], 4.30 [2.80–6.60]; P <.01). 8,14,24,33,34,41 A report by Karia et al 6 also indicated that the RR increases with the size of the involved nerve, with RR (95% CI) of regional recurrence for nerves <0.1 mm in diameter of 5.6 (2.0–15.9) ( P =.001) compared with nerves ≥0.1 mm in diameter (RR [95% CI], 10.4 [4.4–24.7]; P <.001). Interestingly, the AJCC Seventh Edition staging system for cSCC 44 includes PNI as a binary variable for high risk, whereas the BWH staging system includes PNI as a risk factor when the involved nerve is ≥0.1 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of the present study, PNI was analyzed as a binary variable, including 6 articles, and was associated with an RR of local recurrence (RR [95% CI], 4.30 [2.80–6.60]; P <.01). 8,14,24,33,34,41 A report by Karia et al 6 also indicated that the RR increases with the size of the involved nerve, with RR (95% CI) of regional recurrence for nerves <0.1 mm in diameter of 5.6 (2.0–15.9) ( P =.001) compared with nerves ≥0.1 mm in diameter (RR [95% CI], 10.4 [4.4–24.7]; P <.001). Interestingly, the AJCC Seventh Edition staging system for cSCC 44 includes PNI as a binary variable for high risk, whereas the BWH staging system includes PNI as a risk factor when the involved nerve is ≥0.1 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor location on the temple, although not part of the AJCC, UICC, or BWH staging system, 44 was associated with a higher risk of recurrence (RR [95% CI], 3.20 [1.1–9.0]; P =.03) than tumor location on either lip or ear, albeit this finding was based on a single, but relatively large, retrospective analysis by Schmults et al 8 Poor differentiation also was found to have statistically significant association with recurrence (RR [95% CI], 2.66 [1.72–4.14]; P <.01), based on pooled data from 11 studies. 4,6,17,19,2224,34,37,39,41 …”
Section: Discussionmentioning
confidence: 99%
“…Lymph node palpation has a sensitivity of 60 to 75% for detecting lymph node metastasis [1]. Tumor depth and diameter are the most important prognostic factors for determining risk of local recurrence and metastasis [6]. Tumor depth could not be measured in this patient due to treatment with MMS that included curettage to debulk gross tumor to define its extent prior to excision and en face horizontal frozen sections for tumor extirpation.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous squamous cell carcinoma with auricular involvement has a metastatic rate of approximately 15.5% and destruction of cartilage is a significant risk factor for Case Reports in Dermatological Medicine metastatic disease [5][6][7]. The most commonly affected lymph nodes include the parotid, submandibular, submental, and superior cervical nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Known risk factors that increase the risk of morbidity and mortality from CSCC include high-risk location (ie, ears, lips, genitalia, or chronically inflamed or irradiated skin), large tumor diameter, deep vertical invasion, recurrent tumor status, poorly differentiated histology, perineural invasion, and host immunosuppression. 3 Patients with 10 or more tumors had a 10-year cumulative incidence of 36.8% for local recurrence (LR) and 26.3% for nodal metastases (NM), whereas those with only 1 CSCC had LR rates of 3.0% and NM, 2.3%. Patients with between 2 and 9 CSCCs had intermediate rates of both events.…”
mentioning
confidence: 99%